2007
DOI: 10.1002/chem.200601836
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Design of Neutral Molecular Tweezers for Anion Recognition

Abstract: Molecular tweezers are simple molecular receptors that can be characterized by the presence of two flat pincers separated by a more or less rigid tether. They have the ability to form complexes with a substrate molecule by gripping the substrate between the tips of the tweezers in a similar manner to that of mechanical tweezers. Klärner et al. synthesized one of the structurally simplest molecular tweezers, which is reported to bind electrodeficient aromatic and aliphatic substrates as well as organic cations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Apart from the application of π-frameworks in building ion-selective receptors, 1,2,3,4 it has been demonstrated that these interactions are operative in defining the structures of biomolecules, 5,6,7,8,9,10,11,12 and have been used for catalysis. 13,14,15 Furthermore, the extent of ion-π interactions affects the capacity of energy-storage devices such as batteries and supercapacitors based on carbon nanostructures.…”
Section: Ion-π Interactionmentioning
confidence: 99%
“…Apart from the application of π-frameworks in building ion-selective receptors, 1,2,3,4 it has been demonstrated that these interactions are operative in defining the structures of biomolecules, 5,6,7,8,9,10,11,12 and have been used for catalysis. 13,14,15 Furthermore, the extent of ion-π interactions affects the capacity of energy-storage devices such as batteries and supercapacitors based on carbon nanostructures.…”
Section: Ion-π Interactionmentioning
confidence: 99%
“…Molecular tweezers can in principle be divided into three groups: semirigid, [6][7][8][9][10][11][12][13] conformationally labile, [2,[14][15][16][17][18][19][20] and conformationally controlled by hydrogen bonds or metal chelation. [21][22][23] The interaction that mediates the recognition process can, in addition to London dispersion forces, be based on hydrogen-bonding, [24] charge-transfer, [14] ion-p, [8,25] p-p, [1] electrostatic, [8] and coupled interactions. [26] Most common are molecular tweezers with high symmetry, but there are some chiral examples.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] In fact, it has been shown that for example fluorination of benzene can lead to a favorable interaction with anions. [33][34][35][36][37] This effect can be used for designing molecular tweezers for anion recognition. 34 Also, the presence of heteroatoms in the skeleton of aromatic rings can modulate the characteristics of the interaction.…”
Section: Introductionmentioning
confidence: 99%